Implications of patch size and landscape matrix towards native-forest bird species in fragmented forests - Farah Shafawati Mohd-Taib,; Shukor Md-Nor,; Saiful Arif Abdullah, (Malaysian Society of Applied Biology, 2016)
Forest fragmentation has been one of the major issues in urban landscape due to anthropogenic activities. It produces remnants of forest patches, which were originally large and continuous forest. Forest fragmentation will adversely impact on forest fauna diversity. However, the impacts are dependent on the type and characteristic of the forest remnants itself. This study therefore investigated species composition of birds within fragmented forest in the state of Selangor. Six remnants of forest reserves located in the midst of urban landscape that vary in size and landscape matrix were chosen. Methods used were mist-netting and direct observation. A total of 83 species of birds have been recorded in all sites. Native-forest species are species that depends solely on forest for their livelihood. Larger percentage of native-forest species were found in the larger forest compared to smaller forest suggesting that smaller forest are more vulnerable towards invasion of non-forest species. This however is highly supported by the landscape matrix that surrounds the forest. In conclusion, landscape matrix other than forest size were found to be the major factor that influenced the capacity of the forest to maintain more native-forest species. However,further studies need to be carried out at a larger experimental scale to test this theory.